Between The Fame and Joanne: parallels of Lady Gaga’s career with business strategies in competitive environments - Simões, Israel Bueno; Gonçalves, Carlos Alberto; Gonçalves, Márcio Augusto; Silva, Shirlei da Conceição Domingos; Melo, Elimar Silva (Revista de Administração da UFSM, 2019)
In 2018, the American singer Lady Gaga celebrates a decade of the release of her first pop album, The Fame. Ten years ago, the world through a series of more successful and awarded songs of the new generation, capable of breaking records in the disputed music industry. As every product has its lifecycle, Lady Gaga’s music has come to decline, but the singer has been able to react and maintain her competitive edge. In the ups and downs of the market, Lady Gaga is a strong analogy of product changes, amalgamating itself to revitalize her sector, articulating the internal activities, repositioning herself; an image of the challenge that is accomplished in reinventing herself. Thus, from this historical analysis in which the organisation is viewed as a persona, this work reflects on survival strategies in an environment of rapid change and that requires at the same time, identity and constant adaptation. The approach is qualitative and descriptive, based on real cases of the corporate context that work as parallel to the storytelling created from the Gaga case. As a result, a conceptual model on business strategy in competitive environments is presented, which aggregates different schools of thought of the organizational strategy and that can be verified in future researches.